Efektivitas Penggunaan Artificial Intelligence (AI) terhadap Pembelajaran PAI di SMK 2 Bandar Lampung - Fariq Sabili; Waluyo Erry Wahyudi; Chairul Anwar (MAN 4 Kota Pekanbaru, 2026)
The transformation of education in the digital era has encouraged the integration of Artificial Intelligence (AI) into the learning process, including in Islamic Religious Education (PAI). This study aims to analyze the effectiveness of AI utilization in PAI learning at SMK 2 Bandar Lampung. The research employed a quantitative approach with a quasi-experimental design. The population consisted of 735 students who had participated in PAI classes. Samples were selected using a simple random sampling technique through the Spin the Wheel application, with class XI B as the experimental group implementing AI-based learning and class XI A as the control group receiving conventional instruction. The findings indicate that the implementation of AI-based learning has a positive and significant effect on the effectiveness of PAI learning. This is evidenced by the t-test result showing a significance value (Sig. 2-tailed) of 0.002 (< 0.05). Therefore, there is a significant difference in learning outcomes between the two groups.